English Instructional Design For Acceleration Class Of Senior High School Of The Assalaam Islamic Boarding School - Hasanah, Ika Mufidatul; , Prof. Dr. Endang Fauziati, M. Hum; , Dra. Siti Zuhriah Ariatmi, M.Hum (2014)
The objective of this paper is to describe the English instructional design for acceleration class of Senior High School of the Assalaam Islamic Boarding School. Some components involved are the general and specific objectives, syllabus model, type of learning and teaching activity, learner's role, teacher's role and instructional material. The type of this research that is used by the writer is qualitative research. The writer applies the naturalistic approach. The data for this research are field notes taken by the researcher during the observation, documents and interview to related parties. This research is the teacher of acceleration class of senior high school of the Assalaam Islamic Boarding School. The data are analyzed using naturalistic approach by describing some aspects. The study shows that the syllabus which is used by the teacher is the notional- functional syllabus. The objectives of learning are general and specific learning outcomes. The instructional material is divided into two, printed and visual materials. Teacher's roles are as facilitator, manager and organizer, assessor, prompter, observer, investigator and researcher. The learner's roles are as performer, peer-mentor, observer, team member work and writer. The classroom procedure is two patterns namely: BKOF-MOT-JCOT-ICOT and BKOF-JCOT- ICOT. The classroom activities are advance organizer, presentation, discussion, role play, answering questions, reading aloud and conversation practice. The media used are unprinted media such as LCD, screen projector and computer. The evaluation models are multiple choices, essay, matching and oral performance. The kind of evaluation is divided into two; summative evaluation and formative evaluation